2022
DOI: 10.1126/sciadv.abj4526
|View full text |Cite
|
Sign up to set email alerts
|

Toward wide-spectrum antivirals against coronaviruses: Molecular characterization of SARS-CoV-2 NSP13 helicase inhibitors

Abstract: Molecular dynamics simulations are used to unravel the SARS-CoV-2 NSP13 behavior in interaction with natural ligands and inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 39 publications
1
21
2
Order By: Relevance
“…The binding site of the SARS-COV-2 helicase (NSP13) is located between the 1A and 2A domains, comprising important amino acids necessary for ATP binding; Asp374, Glu375, Ser377, Asp401, Gln404, Arg443, Lys288, Ser289, Arg567, and Gly538 (PDB ID: 5RLG ). Experimental and in-silico studies have also been reported targeting the helicase with different molecules [ [106] , [107] , [108] , [109] , [110] , [111] ]. We docked the fortunellin into the active site of the SARS-CoV-2 helicase and found that it achieved a better docking score of −9.8 kcal/mol than the re-docked co-crystallized ligand.…”
Section: Discussionmentioning
confidence: 99%
“…The binding site of the SARS-COV-2 helicase (NSP13) is located between the 1A and 2A domains, comprising important amino acids necessary for ATP binding; Asp374, Glu375, Ser377, Asp401, Gln404, Arg443, Lys288, Ser289, Arg567, and Gly538 (PDB ID: 5RLG ). Experimental and in-silico studies have also been reported targeting the helicase with different molecules [ [106] , [107] , [108] , [109] , [110] , [111] ]. We docked the fortunellin into the active site of the SARS-CoV-2 helicase and found that it achieved a better docking score of −9.8 kcal/mol than the re-docked co-crystallized ligand.…”
Section: Discussionmentioning
confidence: 99%
“…It is also thought to facilitate proper folding and replication of viral RNA [ 23 ]. Inhibition of NSP13 with bismuth salts and other agents blocks viral replication [ 24 27 ]. In addition, NSP13 is capable of suppressing type I IFN production and signaling [ 17 19 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, it is invaluable for assessment of a myriad of computationally identified potential inhibitors of nsp13 from various CoVs. 36 Importantly, the discovery of the druglike small-molecule inhibitors of nsp13 we reported here will enable parallel projects by scientific communities that will accelerate discovery of potent and selective inhibitors of CoV replication and propagation.…”
Section: Discussionmentioning
confidence: 92%